A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae) - Bartlett, Charles R.; Kennedy, Ashley C. (Zootaxa, 2018)
The New World species attributed to the genus Malaxa Melichar (Hemiptera: Fulgoroidea: Delphacidae) are reviewed with special reference to the type species Malaxa acutipennis from the Philippines. We provide an amended diagnosis for Malaxa acutipennis contrasted with the genus delineation presented for Chinese Malaxa, most recently by Hou et al. (2013). We find Malaxa to be an Old World genus and segregate New World species into two new genera, Lamaxa and Xalama, diagnosed most readily by proportions of the antennae and features of the terminalia. Both Lamaxa and Xalama are uncommonly encountered. Lamaxa is distributed widely through the Neotropics, whereas Xalama is heretofore known only from Bolivia and Peru.